To be or not to be... a scientist? - Arnaud Chevalier (Institute for the Study of Labor (IZA), 2012)
Policy makers generally advocate that to remain competitive countries need to train more scientists. Employers regularly complain of qualified scientist shortages blaming the higher wages in other occupations for luring graduates out of scientific occupations. Using a survey of recent British graduates from Higher Education we report that fewer than 50% of science graduates work in a scientific occupation three years after graduation. The wage premium observed for science graduates stems from occupational choice rather than a science degree. Accounting for selection into subject and occupation, the returns to working in a scientific occupation reaches 18% and there is no return to a science degree outside scientific occupations. Finally, scientists working in a scientific occupation are more satisfied with their educational and career choices, which suggests that those not working in these occupations have been pushed out of careers in science.
urn:nbn:de:101:1-201205026219
Keywords: I21; J24; J44; 330; science; graduate; labour market; Wissenschaftler; Akademiker; Arbeitsplatz; Berufswahl; Erwerbsverlauf; Großbritannien